Effect Of Different Muscles On The Quality And Color Stability During Aging Of Hot-Boned Sheep Meat - Kapase, Gangadhar; Kulkarni, Shrikant; M, Kiran; M Govindaiah, Prasad; S M, Kartikesh; G P, Kalmath (Journal of Meat Science, 2024)
This study investigated the impact of conditioning on muscle-specific meat quality in various muscle types, including Vastus lateralis (VL), Gluteo biceps femoris (GBF), Gluteomedius (GM), Longissimus dorsi et lumborum (LL), Psoas major (PM), and Semitendinosus (ST) in sheep. Meat qualityparameters such as water holding capacity (WHC), thiobarbituric acid reactive substance (TBARS), drip loss, and color stability (myoglobin [Mb], met-myoglobin [met-Mb], instrumental color [L*, a* and b*]) were assessed under refrigeration conditions (4±1 º C) on the 0th, 5th, 10th, and 15th day post-mortem. The findings of this study indicated a significant decrease (P<0.05) in myoglobin concentration on the 10th day for VL and GBF muscles, while GM, LD, and ST muscles exhibited this decrease on the 15thday. Notably, met-Mb percentage showed considerable variation (P<0.05) during different post-mortem aging periods among the muscles. TBARS values were significantly higher (P<0.05) on the 5th and 10th days, while water holding capacity and drip loss exhibited a substantial increase (P<0.05), reaching their highest (P<0.05) values on the 15th day post-mortem.Furthermore, the lightness value (L*) increased significantly (P<0.05) in VL, GBF, LL, PM, and ST as the post-mortem aging period progressed. The redness (a*) and yellowness (b*) also increased significantly (P<0.05) with advancing post-mortem aging period. These results provide valuable insights into the effect of conditioning on the meat quality of different muscle types in sheep, shedding light on changes in color stability, myoglobin content, lipid oxidation, and water holding capacity during the post-mortem aging process.